PERKEMBANGAN GERAKAN ISIS DAN STRATEGI PENANGGULANGANNYA (Kasus Perkembangan Awal ISIS di Surakarta) - Joko Tri Haryanto (Harmoni, 2015)
Islamic state of Iraq and Syria (ISIS) movement in the Middle East has spread to Indonesia. One of the areas that have some ISIS followers is ex-residency of Surakarta. This region has been known as a home for Islamic radical groups and some radical religious organizations that flourish. Some of terrorism cases in Indonesia, mostly the terrorists are from Surakarta. This explorative study reveals the early development of ISIS in Surakarta and how to deal with this problem. The result shows that ISIS emerges publicly in July 2014 with some indications such as ISIS symbols in public places (graffiti on city walls and ISIS’ flag) and declaration to support ISIS. ISIS symbols spread to many areas that are affiliated with a famous Islamic radical group and some figures who support ISIS. Socio-political and religious situation in Surakarta contribute to potential radical religious groups that increase ISIS development. Strategic ways to overcome ISIS development are conducting counterdiscourse to ISIS movement, promoting Islam Rahmatan lil’alamin, and creating an Indonesian religious discourse.